Scattered trees as crucial elements in maintaining urban diversity: A case study with canopy ants in a biodiversity hotspot - Mendonça-Santos, Renata Grasiele; Antoniazzi, Reuber; Camarota, Flávio; dos Reis, Yana Teixeira; Viana-Junior, Arleu Barbosa (Acta oecologica (Montrouge), 2023)
Urban environments are characterized by profound differences in abiotic conditions compared to natural environments, which filter one part of the biotic communities that endure living in these environments. A conspicuous element in many cities are scattered trees, often included in urban planning around the world. These trees are key elements for urban ecological processes and services and act as habitat islands, providing resources (i.e., food and shelter) for a considerable arthropod diversity, such as ants. Studies involving ants in urban environments often focus on ground-dwelling ants, and few studies seek to glimpse the ants that occupy scattered trees and, even less, how these ants and trees interact within cities. This study aimed to investigate the ant communities foraging day and night on trees in an urban area inside a biodiversity hotspot, the Brazilian Atlantic Forest. Specifically, we investigated how tree characteristics (tree size, tree isolation, and the tree origin, i.e., native and exotic) modulate ant diversity and ant-plant interactions. We found that the ant species composition is different between day and night, as well as the central core of generalist ant species of day and night interaction networks. The tree size increases beta-diversity among trees only of the nocturnal ant community, while none of the tree characteristics shaped the ant community. This study is the first to address the role of scattered trees in maintaining the diversity of arboreal ants in urban landscapes, focusing on species diversity and their interaction networks. Overall, we provide insights supporting the conservation value of scattered trees in maintaining urban biodiversity. •We investigated arboreal ant communities during day and night in an urban area.•There is a change in the composition of ants in tree-crowns between day and night.•β diversity increased with tree size only for nocturnal community.•The diversity of interactions was similar between diurnal and nocturnal networks.•Different ant species comprised the generalist core of ant-tree networks on day and nighttime.